The effect of passive smoking on the development of respiratory syncytial virus bronchiolitis - (:unkn) unknown (My University, 2000)
In spite of the increasing evidence that passive smoking increases the incidence of respiratory infections and bronchial hyper-responsiveness, the information about whether exposure to sudden heavy smoke enhances the development of acute respiratory infections in children remains inadequate. In this study, to quantitate the level of exposure to environmental tobacco smoke, in 28 children (age ranging 2-18 months) with respiratory syncytial virus (RSV) bronchiolitis and in 30 children (age ranging between 2-15 months) with non-respiratory symptoms, the serum levels of cotinine, the major metabolite of nicotine, were measured at admission to the emergency department. Parents were asked to fill in a questionnaire about the housing conditions and their smoking habits. Serum samples were taken again from the children with RSV bronchiolitis at their second visit at I month after discharge from the hospital. The children with RSV bronchiolitis had higher levels of serum cotinine (mean of 10.8 ng/ml) in the acute stage, compared with post-bronchiolitis stage (mean of 7.4 ng/ml). Moreover, patients admitted with non-respiratory symptoms had significantly lower levels of serum cotinine (mean of 3.9 ng/ ml) than both phases of patients with RSV bronchiolitis. Children with RSV bronchiolitis were found to have higher levels of cotinine when either the mother or both of the parents smoked, than the children with non-smoker parents. In conclusion, children admitted to the hospital with RSV bronchiolitis were shown to be acutely exposed to more cigarette smoke after I month and much more than the children admitted for non-respiratory diseases. These findings may imply that sudden heavy cigarette smoke exposure may predispose to an acute respiratory infection.
Keywords: Bronchiolitis; Cotinine; Passive smoking; Respiratory syncytial virus